Ranking Regimes and the Production of Knowledge in Academia: (Re)shaping Faculty Work? - Gonzales, Leslie D; Núñez, Anne-Marie (Education Policy Analysis Archives, 2014)
In this integrated review of literature, we address a powerful movement among interrelated organizations that we call the “ranking regime.” We argue that the ostensive purpose of this regime is to identify “world class” universities, and thus to organize post-secondary education into a competitive transnational market. Although extant research has addressed how rankings are reshaping the field of higher education, there is little work that addresses the influence of rankings on the evaluation of faculty work and the production of knowledge. Thus, we review existing studies that have focused on the intersection of this ranking regime, faculty work, and faculty evaluation in order to assess the implications of the ranking regime for the production of knowledge within academia and for faculty evaluation. We argue that the ranking regime affects the production and evaluation of knowledge by promoting individualism, standardization, commodification, and homogenization. We offer policy and practice implications as well as directions for future research.